2021
DOI: 10.1002/adma.202107150
|View full text |Cite
|
Sign up to set email alerts
|

Shielding Ferritin with a Biomineralized Shell Enables Efficient Modulation of Tumor Microenvironment and Targeted Delivery of Diverse Therapeutic Agents

Abstract: Ferritin (Fn) is considered a promising carrier for targeted delivery to tumors, but the successful application in vivo has not been fully achieved yet. Herein, strong evidence is provided that the Fn receptor is expressed in liver tissues, resulting in an intercept effect in regards to tumor delivery. Building on these observations, a biomineralization technology is rationally designed to shield Fn using a calcium phosphate (CaP) shell, which can improve the delivery performance by reducing Fn interception in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 52 publications
0
25
0
Order By: Relevance
“…It is known that the high expression of TfR1 in the liver may interfere with HFn accumulation in tumors. Indeed, it has been observed that a co-culture with liver cells may cause reduced uptake efficiency by tumor cells, thus negatively affecting HFn’s delivery to the tumor . To overcome this limitation, a biomineralization strategy of shielding HFn with a calcium phosphate (CaP) shell has been proposed.…”
Section: Chemical Modifications Of H-ferritin Nanocagesmentioning
confidence: 99%
See 2 more Smart Citations
“…It is known that the high expression of TfR1 in the liver may interfere with HFn accumulation in tumors. Indeed, it has been observed that a co-culture with liver cells may cause reduced uptake efficiency by tumor cells, thus negatively affecting HFn’s delivery to the tumor . To overcome this limitation, a biomineralization strategy of shielding HFn with a calcium phosphate (CaP) shell has been proposed.…”
Section: Chemical Modifications Of H-ferritin Nanocagesmentioning
confidence: 99%
“…Indeed, it has been observed that a co-culture with liver cells may cause reduced uptake efficiency by tumor cells, thus negatively affecting HFn’s delivery to the tumor. 23 To overcome this limitation, a biomineralization strategy of shielding HFn with a calcium phosphate (CaP) shell has been proposed. Indeed, the presence of a mineral-reinforced coating is expected to enhance HFn’s serum stability, as likewise observed for CaP-mineralized micelles.…”
Section: Chemical Modifications Of H-ferritin Nanocagesmentioning
confidence: 99%
See 1 more Smart Citation
“…e TEM images of Fn and Fn@CaP. f Elemental mapping analysis (left panel) and energy dispersive spectroscopy (EDS) analysis (right panel) of Fn@CaP [ 70 ]. Copyright 2022, Wiley–VCH …”
Section: Classification and Physicochemical Properties Of Calcium Com...mentioning
confidence: 99%
“…For example, Wang and co-workers coated ferritin (Fn) with CaP to enclose Fn within a “temporary protective shell” by biomineralization technology to increase the enrichment of Fn in the target region, and the TME-responsive dissolution of CaP shell can not only neutralize tumor acidity but also induce intratumor immune regulation and tumor calcification (Fig. 4 d–f) [ 70 ]. Due to its well-behaved biocompatibility, biodegradability, and controlled release behavior, CaP nanoplatform provides a profound paradigm for effective cancer therapy and has great potential for in clinical transformation.…”
Section: Classification and Physicochemical Properties Of Calcium Com...mentioning
confidence: 99%